Disaster management leadership and intrinsic motivation towards improving human resources performance of the regional disaster management agency of Jepara Regency - Windi Novia Ratri Wardhani (Universitas Pekalongan, 2025)
This study aims to analyze the impact of disaster management leadership on human resources (HR) performance and their intrinsic motivation at the Regional Disaster Management Agency (BPBD) of West Kotawaringin Regency. Employing an explanatory research approach, this study involved all HR at the BPBD of West Kotawaringin Regency as the population, with a total sample of 53 respondents, selected through a census sampling technique. Primary data was collected using questionnaires containing questions related to the variables of disaster management leadership and HR performance, measured with a Likert scale from 1 to 5, and analyzed using the Partial Least Squares (PLS) statistical tool. The findings indicate that disaster management leadership has a positive and significant effect on HR performance and their intrinsic motivation at the BPBD of West Kotawaringin Regency. Furthermore, intrinsic motivation was also found to have a positive and significant effect on HR performance. These findings highlight the importance of effective leadership in disaster management to enhance HR performance and intrinsic motivation, which are crucial in disaster mitigation. This study provides new insights into the dynamics of leadership and motivation in the context of disaster management, offering a significant contribution to disaster management practices in Indonesia, especially at the BPBD of West Kotawaringin Regency.